The structural properties of Sn-doped zinc oxide synthesized by hot-tube thermal evaporation - Suhaimi S.; Sakrani S.; Hashim M.A.; Nadhrah Md Yatim (American Institute of Physics Inc., 2024)
Indexed by WOS/ Scopus